2018
DOI: 10.1021/acs.biochem.8b00978
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine Disulfide Traps Reveal Distinct Conformational Ensembles in Dengue Virus NS2B-NS3 Protease

Abstract: The dengue virus protease (NS2B-NS3pro) plays a critical role in the dengue viral life cycle, making it an attractive drug target for dengue-related pathologies, including dengue hemorrhagic fever. A number of studies indicate that NS2B-NS3pro undergoes a transition between two widely different conformational states: an “open” (inactive) conformation and a “closed” (active) conformation. For the past several years, the equilibrium between these states and the resting conformation of NS2B-NS3pro have been debat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…This fast cleavage validated the amino acid sequences of our linkers as well as the application of "unlinked" versions of both recombinant DENV-2 and ZIKV proteases, in which the NS2B and NS3 regions were produced as independent polypeptides. This choice was based on our own demonstration that the "unlinked" version of DENV-2 protease rests predominantly in a "closed," active conformation, in contrast with the less active, relaxed conformation, adopted by the frequently used "linked" construct, in which NS2B and NS3 polypeptides are attached by a nine-amino acid linker (31).…”
Section: Discussionmentioning
confidence: 99%
“…This fast cleavage validated the amino acid sequences of our linkers as well as the application of "unlinked" versions of both recombinant DENV-2 and ZIKV proteases, in which the NS2B and NS3 regions were produced as independent polypeptides. This choice was based on our own demonstration that the "unlinked" version of DENV-2 protease rests predominantly in a "closed," active conformation, in contrast with the less active, relaxed conformation, adopted by the frequently used "linked" construct, in which NS2B and NS3 polypeptides are attached by a nine-amino acid linker (31).…”
Section: Discussionmentioning
confidence: 99%
“…There is an ongoing debate in the literature whether the linked or unlinked protease constructs are more suitable for drug discovery campaigns (Kang et al 2017;Nitsche 2018;Nitsche et al 2014). The linked constructs tend to be more stable, whereas the unlinked constructs are thought to resemble a state that is closer to the native one (de la Cruz et al 2014;Hill et al 2018;Li et al 2017a). Recent studies with Zika virus protease suggest that the covalent linker may prevent the formation of the catalytically active complex to a certain degree (Li et al 2017a), whereas no significant differences for inhibitor binding could be observed between linked and unlinked Zika virus protease constructs (Nitsche et al 2019).…”
Section: Constructs For Drug Discoverymentioning
confidence: 99%
“…After initial challenges with heterogeneity in sample preparations, most reports concluded that both, the dengue and West Nile virus proteases, predominately adopt the closed conformation in solution, regardless of the construct (linked or unlinked) or the presence of an inhibitor (de la Cruz et al 2014Cruz et al , 2011Kim et al 2013;Su et al 2009). Observed conformational flexibilities may relate to exchange phenomena between open and closed states, the extent of which can differ between constructs (Hill et al 2018). In the case of Zika virus protease, NMR experiments indicated sample heterogeneity promoted by the Gly 4 SerGly 4 linker and ligand-binding events (Li et al 2017a;Mahawaththa et al 2017).…”
Section: Open or Closed?mentioning
confidence: 99%
“…An outbreak occurred during 2015-2016 and over 2 million people were affected [4][5][6][7]. Effort has been made to develop antivirals and vaccines to combat the virus while no specific medical treatment is available [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%